Alcohol use and dependence among the students attending ege university faculty of science - Yiğit, Şenay; Khorshid, Leyla (Journal of Dependence, 2006)
Objective: Alcohol use and dependence are some of the most important health problems among university students. This descriptive study was carried out to investigate alcohol use and dependence in this population.Method: The study sample consists of 300 students attending the Faculty of Science in Ege University. A questionnaire form and Michigan Alcoholism Screening Test were used in collecting the data. Data were analysed by using Chi-square test.Results: It was found that 76% of students were using alcohol, 8.8% of them had alcohol dependence and 14% had alcohol abuse. It was determined that the rate of alcohol dependence was significantly higher among students in 17-19 age group, and the rate of alcohol use was significantly lower among students who stayed in dormitory.Conclusion: Alcohol using and dependence is high in university students.
Keywords: Alcohol; alcohol use; alcohol dependence; university student